Standardization of Small Businesses: A Feasibility Study of Restaurants in Enrekang Regency - Muhammad Rakib; Muhammad Arifin (Program Pascasarjana Universitas Negeri Makassar, 2018)
The purpose of this study was to determine the level of feasibility of restaurant businesses in Enrekang Regency based on restaurant standards that have been established based on Minister of Tourism and Creative Economy Regulations. This research is an evaluation research on meeting the standards of home eating business seen from product standards, service, and management. The study was conducted in 8 (eight) restaurants in Enrekang Regency. Data was collected through assessment instruments about the standard business of restaurants. Data were analyzed using descriptive analysis. The results showed that restaurants in Enrekang District were sufficient to meet product, service and management standards as intended in the Minister of Tourism and Creative Economy Regulation No. 12 of 2014